2017
DOI: 10.1128/msphere.00201-17
|View full text |Cite
|
Sign up to set email alerts
|

Long Persistence of a Streptococcus pneumoniae 23F Clone in a Cystic Fibrosis Patient

Abstract: Streptococcus pneumoniae is a common resident in the human nasopharynx. However, carriage can result in severe diseases due to a unique repertoire of pathogenicity factors that are rare in closely related commensal streptococci. We investigated a penicillin-resistant S. pneumoniae clone of serotype 23F isolated from a cystic fibrosis patient on multiple occasions over an unusually long period of over 3 years that was present without causing disease. Genome comparisons revealed an apparent nonfunctional pneumoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…There is evidence, however, that transfer of homologous DNA seems to occur between S. mitis and S. oralis (Kilian et al, 2008). A recent report of in vivo interspecies gene transfer by Rieger et al (2017) revealed the acquisition of a pbp2x mosaic gene of S. pneumoniae by a S. mitis strain, supporting a “two-way street” in gene exchange between the two species. Since the pbp gene is close to the capsule locus, recombination events in this region may also facilitate the transfer of capsule genes from one species to the other.…”
Section: Horizontal Gene Transfer In Streptococcus Pneumoniae and Clomentioning
confidence: 93%
“…There is evidence, however, that transfer of homologous DNA seems to occur between S. mitis and S. oralis (Kilian et al, 2008). A recent report of in vivo interspecies gene transfer by Rieger et al (2017) revealed the acquisition of a pbp2x mosaic gene of S. pneumoniae by a S. mitis strain, supporting a “two-way street” in gene exchange between the two species. Since the pbp gene is close to the capsule locus, recombination events in this region may also facilitate the transfer of capsule genes from one species to the other.…”
Section: Horizontal Gene Transfer In Streptococcus Pneumoniae and Clomentioning
confidence: 93%
“…The genes coding for these low affinity PBPs are mosaic genes formed by recombination between strains, in many cases between pneumococcus and other streptococcal species ( Dowson et al, 1989 ; Sibold et al, 1992 ; Chi et al, 2007 ; Sauerbier et al, 2012 ; Mousavi et al, 2017 ). A recent study captured a gene exchange event between a strain of S. mitis and pneumococcus isolated from a longitudinal study in a cystic fibrosis patient ( Rieger et al, 2017 ). An additional example for a functional class of genes that undergoes exchange across species is peptides implicated in cell-cell communication.…”
Section: Gene Transfer In the Pneumococcus: Implications For The Pangmentioning
confidence: 99%
“…It is assumed that gene exchange by transformation has contributed significantly to the increasing incidence of penicillin-resistant S. pneumoniae [ 163 , 164 ], and this is probably also the case in S. suis . In this context, the acquisition of a pbp2x gene of S. pneumoniae by a Streptococcus mitis strain has been reported [ 165 ]. Thus, exchange of pbp sequences could quickly generate β-lactam-resistant strains by introducing multiple simultaneously occurring substitutions in a single gene.…”
Section: Transfer Of Antibiotic-resistance Genesmentioning
confidence: 99%